Method for applying a coating to a surface of a mullite material, a mullite material having a coating, and a gas turbine module
Patent Information
- Application Number
- JP2021568977
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-20
- Filing Date
- 2020-05-19
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-05-19
Smart Images

Figure 0007632789000001 
Figure 0007632789000002 
Figure 0007632789000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for applying a coating onto a surface of a mullite material, a mullite material having a coating, and a gas turbine module. [Background technology]
[0002] In modern gas turbines, silicon- and aluminum-containing materials are used in the area of the combustion chamber as combustion chamber bricks and also in other gas turbine modules. These materials are usually referred to as mullite as a whole, but in addition to the actual mullite phase with chemical composition 3(Al2O3) × 2(SiO2), they may also contain phases of other Al2O3-SiO2 compounds and phases of pure Al2O3 with corundum structure (α-Al2O3).
[0003] Furthermore, many ceramic fiber composites contain mullite-containing fibers. Therefore, in the following, the term "mullite material" is used for all materials containing Al2O3-SiO2 up to materials consisting almost exclusively of Al2O3. The concept of mullite material also includes so-called Ox-Ox materials, which are aluminum oxide-based ceramic matrix composite materials (CMCs). Figure 1 shows an optical micrograph of a cut surface of a mullite material, in which the different phases that can occur at different grain sizes are marked.
[0004] In addition to the differences in the phases of the materials, another characteristic of mullite materials is the variety of grain sizes, which can be introduced or generated during synthetic manufacturing by mixing of the starting materials and high temperature sintering.
[0005] This mullite material has excellent mechanical strength and chemical stability, even at very high temperatures such as those that can occur in the combustion chamber of a turbine.
[0006] However, the mullite material has the disadvantage that it is attacked by hot steam, which can form volatile compounds with the silicon contained in the mullite material. This results in loss of silicon from the surface of the mullite material, for example in a combustion chamber brick or other component, and can be released from the mullite material as particles lose adhesion and are flaked off. These flaked off particles increase erosion and result in wear of components such as turbine blades and subsequent guide ring segments in the turbine area.
[0007] In turbine components, thick protective layers can be thermally sprayed to prevent erosion by particles (Patent Document 1). However, even if this protective layer has a good bond with and adheres well to the mullite material, it can peel off under high thermomechanical loads and fail after a relatively short period of operation. This is especially true for protective layers that do not chemically react with the mullite material or have a thermal expansion coefficient that differs significantly from that of the mullite material. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] European Patent Application Publication No. 1 780 294 A1 Summary of the Invention [Problem to be solved by the invention]
[0009] The object of the present invention is to indicate a coating method and a coating which allows at least alleviating the above-mentioned disadvantages. [Means for solving the problem]
[0010] This problem is solved by the subject matter of the independent claims. The dependent claims contain embodiment variants of these solutions according to the invention.
[0011] A key cause of poor adhesion or bonding on mullite materials is the variety of grain sizes and / or fibers, as well as the variety of phases, particularly the diversity of phases. Currently available materials and methods can optimize adhesion for only one phase, e.g., α-Al2O3 (corundum structure) or 3(Al2O3)×2(SiO2) (mullite structure), but cannot optimize adhesion for multiple phases simultaneously due to the different properties of these phases.
[0012] An additional problem is matching the layer materials to the mullite material so that chemical bonding is possible, and the various phases of the mullite material also have a detrimental effect in that respect, since different chemical reactions must take place.
[0013] Finally, the typical method of applying a protective layer by thermal spraying involves a heating step to achieve good adhesion, which is intended to cause diffusion of elements at the interface between the mullite material and the thermally sprayed protective layer. However, at least one component of the mullite material, namely corundum, is known to be a good diffusion barrier, thus preventing the typical method of improving adhesion via a diffusion process.
[0014] The basic idea of the present invention is therefore to pretreat the surface of the mullite material before applying the coating, so that substantially only one material phase is present at the surface, and with reference to the properties of this material phase the coating to be applied can be adapted to obtain the best possible bonding or adhesion.
[0015] The method of the present invention for applying a coating onto a surface of a mullite material includes the steps of pretreating the surface of the mullite material using a plasma chemical process in which hydrogen molecules are excited to produce plasma activated hydrogen, e.g., hydrogen atoms and / or ionized hydrogen molecules, and applying an aluminum oxide-containing layer onto the pretreated surface of the mullite material using a PVD method.
[0016] For the concept of "mullite material", please refer to the definition given at the beginning. The mullite material is a substrate on whose surface a coating is applied after pretreatment. Similarly, the mullite material can represent a coating on another material.
[0017] The coating may have further layers in addition to the aluminum oxide-containing layer, e.g., adhesion layers, cover layers, thermal insulation layers, etc. Preferably, the aluminum oxide-containing layer is applied directly to the pretreated surface of the mullite material, i.e. without any intermediate layers.
[0018] To pre-treat the surface of the mullite material, the surface is subjected to a plasma-chemical process in vacuum (pressure range of 0.001 mbar to 1 mbar, preferably 0.05 mbar to 0.1 mbar) in which hydrogen molecules are excited to give hydrogen atoms and ionized hydrogen molecules.
[0019] The plasma removes silicon very gently and only in the top atomic layer from the silicon-containing phase of the mullite material by forming volatile Si-H compounds, which are then pumped out of the vacuum using a pumping system. At the same time, impurities such as carbon, hydrocarbons or other elements are removed and pumped out on the pure Al-O phase and in all other areas of the surface of the mullite material.
[0020] The pretreatment results in a pretreated surface of the mullite material that comprises essentially only α-Al2O3, i.e., aluminum oxide with a corundum structure.
[0021] Optionally, before pretreating the surface of the mullite material using a plasma-chemical process, the surface can be infiltrated with an aluminum-containing material, such as YAG (yttrium aluminum garnet). This advantageously reduces the porosity of the surface by at least partially filling existing pores with the aluminum-containing material. This infiltration results in a more homogeneous surface, so that the subsequently applied aluminum oxide-containing layer cannot "penetrate" into the pores and the surface is better covered overall. In other words, the method according to the invention is also suitable for applying a coating onto the surface of a material that has previously been infiltrated with an aluminum-containing material.
[0022] In a further method step, an aluminum oxide-containing layer is applied onto the pretreated surface of the mullite material using a PVD method (PVD=Physical Vapour Deposition in English, Physical Vapour Deposition in German), for example a vapor deposition method, such as reactive cathodic spark deposition or sputtering.
[0023] Both of these PVD processes utilize a target from which material is ablated and deposited onto the surface of the mullite material. The target contains aluminum and optionally other elements, such as chromium, titanium, hafnium, yttrium, erbium, silicon, and / or zirconium, which are to be included in the layer to be applied. The PVD process is carried out in a reactive oxygen-containing environment, resulting in the oxidation of aluminum and possibly further elements, resulting in the deposition of an aluminum oxide-containing layer. Alternatively, the aluminum oxide-containing layer can be applied by radio frequency sputtering of an aluminum oxide-containing target.
[0024] Preferably, the aluminum oxide-containing layer is applied onto the pretreated surface of the mullite material by reactive cathodic spark deposition, whereby a target material is deposited which is connected as a cathode in the spark deposition, the deposition being carried out in vacuum under a controlled oxygen partial pressure which can be set by a suitable oxygen gas flow.
[0025] The application of the aluminum oxide-containing layer onto the pretreated surface of the mullite material is preferably carried out at a substrate temperature in the range between 550° C. and 650° C., particularly preferably at a substrate temperature of 600° C. However, it is also possible to reduce this temperature to below 300° C. or to apply the layer at a higher temperature.
[0026] The above-mentioned PVD method is advantageous because it allows the application of a uniform aluminum oxide-containing layer in only one process step. Furthermore, the preferred layer thickness in the range between 0.5 μm and 50 μm can be achieved with high precision. Furthermore, reactive cathodic spark deposition is characterized by a high robustness; therefore, special adjustments to avoid target poisoning are usually not necessary. Furthermore, the metal vapor generated during reactive cathodic spark deposition is highly ionized, which contributes to good adhesion of the layer.
[0027] The interface region between the mullite material and the aluminum oxide-containing layer produced by this method has spike-like structures of aluminum oxide-containing material, preferably aluminum oxide, which improves adhesion or bonding of the aluminum oxide-containing layer onto the mullite material.
[0028] Preferably, the target also comprises metallic chromium. For example, targets with an elemental distribution of 70 / 30 (Al / Cr) can be used. The proportion of chromium in the target promotes the formation of a corundum structure in the Al-Cr-O solid solution formed, even at relatively low temperatures below 500°C. By varying the proportion of chromium in the target, the lattice constant of the Al-Cr-O solid solution structure in the aluminum oxide-containing layer that can be applied can be adjusted to a range between corundum and escolite. The corundum structure is characterized by a high thermal stability.
[0029] In this case, Vegard's law can be applied, which states that the lattice constant of a crystal changes linearly depending on the ratio of components.
[0030] This Al-Cr-O solid solution structure can exist in different grain sizes, which are influenced by the process conditions of the PVD method (e.g., chromium percentage in the target, oxygen partial pressure, substrate temperature, etc.) and can be controlled accordingly. As a result, the applied aluminum oxide-containing layer can, depending on the process conditions, for example, be x-ray amorphous or clearly show a corundum structure in x-ray analysis, with the position of the Bragg peak corresponding to the chromium percentage being between that of pure corundum and that of escolite.
[0031] Preferably, the aluminum oxide-containing layer is applied as a substantially single-phase layer, for example as a solid solution with a corundum structure. The advantage of this is that the protective effect of the layer can last for a longer period, since the properties of the layer are homogeneous. Above all, this solid solution structure is thermally stable.
[0032] More preferably, the crystal structure of the aluminum oxide-containing single-phase layer corresponds to a corundum structure or passes at higher temperatures into a corundum structure. If the aluminum oxide-containing layer also contains chromium, this layer is preferably applied as a single-phase layer with a corundum solid solution structure.
[0033] Furthermore, the aluminum oxide-containing layer can have macroparticles of metal, so-called droplets, which can occur, for example, during reactive cathodic spark deposition. When using a chromium-containing target, the macroparticles can have a higher proportion of chromium than the target, i.e., chromium can accumulate in the macroparticles. When the droplets are oxidized, they can go directly into solid solution. This oxidation process is advantageous because it allows possible grain boundaries to be inferred.
[0034] According to various embodiment variants, the aluminum oxide containing layer can comprise chromium, titanium, hafnium, yttrium, erbium, silicon and / or zirconium. Preferably, the aluminum oxide containing layer can comprise chromium. For this purpose, the above-mentioned elements can be present in the target used for applying the layer. Other elements can also be present to promote certain properties.
[0035] See above for the optional component chromium: these elements may serve, for example, to adapt the properties of the layer to the mullite material to be coated or to influence the properties of further layers.
[0036] If a substantially single-phase layer is to be applied onto the surface of the mullite material, the above-mentioned additional elements should not appreciably exceed their solubility limits in aluminum, in other words, the proportion of the elements may approach, but not exceed, or at most only slightly exceed, their solubility limits in aluminum.
[0037] Alternatively, a higher proportion of additional elements can be used to adapt the material properties to specific requirements, for example to match the thermal expansion coefficient of the layer to be applied with that of the substrate.
[0038] The aluminum oxide-containing layer can be applied in a layer thickness between 0.5 μm and 50 μm, which can be selected depending on, for example, the surface quality, e.g., roughness, of the mullite material, so that the properties of the coated mullite material can be improved.
[0039] According to a further embodiment, the method may include heat treating the applied aluminum oxide containing layer at a temperature in the range between 900° C. and 1400° C. for a period of between 15 and 60 minutes, for example at a temperature of about 1200° C. for about 30 minutes.
[0040] Lower temperatures result in longer removal periods. Heat treatment can improve the bonding of the applied layer to the substrate and, if the applied layer contains chromium, can also lead to diffusion of chromium to the layer surface and deposition of the chromium oxide formed.
[0041] This process leaves behind fine porosity which greatly improves the ductility tolerance of the layer.
[0042] Instead of a heat treatment, the applied aluminum oxide-containing layer can be post-treated using oxygen plasma. In other words, the plasma oxidation of the applied layer can be carried out in an oxygen atmosphere, whereby the oxygen is activated by the plasma. Such a post-treatment can be advantageously carried out immediately after the application of the aluminum oxide-containing layer on the surface of the mullite material, without the need to break the vacuum. As a result, such a post-treatment can be carried out quickly and at low cost.
[0043] Another aspect of the invention relates to a mullite material comprising an aluminum oxide-containing layer disposed on a surface of the mullite material, with spike-like structures formed at an interface between the mullite material and the aluminum oxide-containing layer, the spike-like structures having tips directed into the aluminum oxide-containing layer.
[0044] The mullite material according to the present invention can be obtained, for example, by the method described above. The spike-like structure has a substantially triangular cross section (parallel to the layer thickness), for example, an isosceles triangle. When viewed three-dimensionally, the spike-like structure can have, for example, an approximately conical geometric shape with a substantially circular base. The substantially triangular shape can be verified, for example, by scanning electron micrographs or transmission electron micrographs after sample preparation as is customary in the art.
[0045] The spike-like structures essentially start at the interface between the mullite material and the aluminum oxide-containing layer, i.e., at the surface of the mullite material before coating, and taper as the thickness of the aluminum oxide-containing layer increases, i.e., form a tip that is directed into the aluminum oxide-containing layer. Typical dimensions of the spike-like structures are a width b (measured parallel to the interface between the mullite material and the aluminum oxide-containing layer) between 50 nm and 200 nm, and a height h (measured parallel to the thickness of the aluminum oxide-containing layer) between 100 nm and 500 nm. The dimensions can be derived, for example, by evaluating scanning or transmission electron micrographs.
[0046] This spike-like structure allows the aluminum oxide-containing layer to bond very well to the mullite material, so that the coated mullite material is characterized by very high thermal stability and a long service life, which can be advantageously used in high-temperature applications, such as gas turbines.
[0047] The aluminum oxide-containing layer acts as a protective layer so that the mullite material cannot be attacked by hot steam, thereby preventing particle ejection from the surface and the resulting erosion caused by the ejected particles.
[0048] Preferably, the spike-like structures comprise an aluminum-containing material or consist of aluminum oxide, which results in a particularly good adhesion or bond between the mullite material and the aluminum oxide-containing layer.
[0049] The thickness of the aluminum oxide-containing layer can be between 0.5 and 50 μm, preferably between 5 and 20 μm. With this thickness range, particularly good protection of the mullite material at high temperatures can be achieved.
[0050] According to various embodiment variants, the aluminum oxide-containing layer is substantially single-phase. Moreover, this aluminum oxide-containing layer may comprise metal macroparticles. Furthermore, the aluminum oxide-containing layer may comprise chromium, titanium, hafnium, yttrium, erbium, silicon and / or zirconium. With regard to these embodiment variants, reference is made to the above-mentioned explanations and advantages mentioned above with regard to the method.
[0051] Another aspect of the invention relates to a gas turbine module, e.g. a combustion chamber brick, comprising the mullite material according to the invention. The gas turbine module may be part of a gas turbine. In the field of gas turbine modules, the use of the mullite material according to the invention is particularly advantageous, since otherwise damage caused by erosion by particles may cause long downtimes and high repair costs. The gas turbine module according to the invention has a longer service life than a gas turbine module that does not comprise the mullite material according to the invention, and therefore allows shorter maintenance intervals.
[0052] The invention is explained in more detail below on the basis of the figures and the description of the figures. [Brief description of the drawings]
[0053] [Figure 1] 1 is an optical microscope photograph of a cut surface of a mullite material. [Diagram 2] FIG. 2 is a schematic diagram of a coated mullite material. [Diagram 3] 1 is an example of a flowchart of a coating method. [Figure 4]1 is a scanning electron micrograph (low magnification) of a cut surface of a mullite material having a coating. [Diagram 5] 4 is a schematic cross-sectional view of the interface region between the mullite material and the coating. [Figure 6] FIG. 2 is a schematic cross-sectional view showing the dimensional ratio of a spike-shaped structure. [Figure 7] 1 is a scanning electron micrograph (high magnification) of a cut surface of a mullite material with a coating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0054] FIG. 1 is an optical microscope photograph of a cut surface of a mullite material 3, depicting the various phases that may occur at different grain sizes. It can be seen that the corundum structure phase, labeled "α-aluminum oxide" in FIG. 1, is formed in triangular form, and that the mullite structure, labeled "mullite (3Al2O3×2SiO2)" in FIG. 1, is formed in elongated form. As already mentioned, such materials are generally referred to herein as mullite material 3. This mullite material 3 can be used, for example, in the manufacture of combustion chamber bricks for gas turbines.
[0055] 2 shows a schematic representation of a coated mullite material 3 which can be obtained by the method according to the invention. Directly on the surface 2 of the mullite material 3 pretreated by means of a plasma-chemical process is arranged an aluminium oxide-containing layer 4, which forms a coating 1. Optionally, the coating 1 can have further layers, which are not shown in FIG.
[0056] The aluminium oxide containing layer 4 may consist, for example, of aluminium oxide, but may also contain other elements such as chromium. The aluminium oxide containing layer 4 was applied using a PVD method, preferably reactive cathodic spark deposition.
[0057] A method of applying a coating 1 onto a surface 2 of a mullite material 3 will now be described with reference to FIG.
[0058] In a first treatment step S1, the surface 2 of the mullite material 3 is pretreated. For this purpose, a plasma-chemical process is used, which excites hydrogen molecules to generate plasma-activated hydrogen, which acts on the surface 2. This removes silicon from the uppermost atomic film of the silicon-containing phase, resulting in a surface 2 that essentially comprises only α-Al2O3 of various grain sizes.
[0059] Specifically, for example, the following pretreatment can be performed: First, the substrate is placed in a coating chamber equipped with a coating device. In order to generate plasma activated hydrogen (reactive hydrogen plasma), the coating chamber is equipped with a further device that is composed of a cathode and an anode and can generate an arc discharge in addition to the coating device.
[0060] Depending on the application, the anode can be insulated from the coating chamber, i.e. also from earth, or can be at the same potential as the coating chamber, or the anode can be realized by a conductive substrate holder. The arc discharge is operated with a rare gas, typically argon. The space between the cathode and the anode, preferably close to the cathode, is filled with a 1×10 -4 mbar and 1×10 -2 The flow of argon is selected to generate a pressure in the coating chamber between 100 and 2000 mbar. An arc discharge is then ignited by a suitable ignition device. Such an arc discharge is characterized by a high discharge current (10 A - 400 A) and a low discharge voltage (20 V - 40 V).
[0061] After the arc discharge is ignited, hydrogen, a reactive gas, is added to the arc discharge to activate it, thereby increasing the number of times the arc discharge reaches 5×10 -3 mbar and 5×10 -2The hydrogen gas flow is selected so that a total pressure of between 1000 and 10000 mbar is produced in the coating chamber. In the arc discharge, the added hydrogen gas dissociates, atomizes, is excited and ionized. This generates highly reactive hydrogen, which can react with elements on the substrate surface to be coated and with elements such as Si or C form volatile gaseous compounds that can be pumped out.
[0062] This surface pretreatment in hydrogen plasma results in a surface that is free of both silicon and undesirable carbon-based impurities present at the surface of the mullite material. The cleaning depth of such a method is limited to the depth of attack of the active hydrogen, i.e., typical penetration depths in the range of 10 nm to 100 nm. Such surface modification close to the substrate is of course not sufficient to achieve continuous protection against volatilization of silicon, for example under water vapor at high temperatures (above 1000 °C).
[0063] After hydrogen plasma treatment, it is essential that the mullite material is protected with an additional layer that is inert to reactive hydrogen.
[0064] In a subsequent method step S2, therefore, an aluminium oxide-containing layer 4 is applied onto the pretreated surface 2. This coating is preferably carried out immediately after the pretreatment in the same coating chamber without breaking the vacuum, for example using PVD methods such as reactive cathodic spark deposition or sputtering.
[0065] After method step S2, the applied aluminum oxide-containing layer 4 can be post-treated. There are two possibilities for this: in method step S3, the aluminum oxide-containing layer 4 is either subjected to a heat treatment at, for example, 1200° C. for 30 minutes, or in method step S4, the aluminum oxide-containing layer 4 is oxidized by means of oxygen plasma.
[0066] 4 is a scanning electron micrograph of a cut surface of an example of a mullite material 3 having an aluminum oxide-containing layer 4 applied onto a surface 2 of the mullite material 3 using reactive cathodic spark deposition. The layer thickness 5 is about 2 μm. The white area above the aluminum oxide-containing layer 4 is caused by over-exposure of the boundary area (due to the substrate preparation) during the making of the scanning electron micrograph and has no physical meaning.
[0067] Figure 5 is a schematic enlargement of the area outlined in black in Figure 4 in the boundary region 7 between the mullite material 3 and the aluminium oxide containing layer 4. Clearly visible are the spike-like structures 6, consisting essentially of aluminium oxide, with their tips 8 directed into the aluminium oxide containing layer 4. The spike-like structures 6 significantly improve the bond or adhesion between the mullite material 3 and the aluminium oxide containing layer 4.
[0068] FIG. 6 shows the dimensional ratios of the spike-like structures 6. It can be seen that the spike-like structures 6 start at the interface 7 between the mullite material 3 and the aluminum oxide-containing layer 4 (which corresponds to the surface 2 before coating) in the boundary region 7 between the mullite material 3 and the aluminum oxide-containing layer 4, and their tip 8 is directed into the aluminum oxide-containing layer 4. In the cross section shown, the spike-like structures 6 have a substantially isosceles triangular shape. The width b of the spike-like structures 6 is between 50 and 200 nm, and the height h is between 100 and 500 nm. The layer thickness 5 of the aluminum oxide-containing layer 4 can be, for example, about 1.5 μm.
[0069] 7 is a scanning electron micrograph of a mullite material 3 having an aluminum oxide-containing layer 4 disposed on a surface 2. The aluminum oxide-containing layer 4 is substantially single phase and comprises chromium in addition to aluminum and oxygen.
[0070] In the boundary region 7 between the mullite material 3 and the aluminum oxide containing layer 4, spike-like structures 6 are found, which originate at the interface or surface 2 between the mullite material 3 and the aluminum oxide containing layer 4. The tips 8 of the spike-like structures 6 are directed into the aluminum oxide containing layer 4. The width b of the spike-like structures 6 is between 50 and 200 nm, while the height h is between 100 and 500 nm.
Claims
1. A method for applying a coating (1) onto a surface (2) of a material, comprising the steps of: a step (S1) of pretreating the surface (2) of the material using a plasma-chemical process in which hydrogen molecules are excited so as to produce plasma-activated hydrogen; applying (S2) an aluminium oxide-containing layer (4) onto the pretreated surface (2) of the material using a PVD method; Including, The material is 3(Al 2 O 3 ) × 2 (SiO 2 ) and / or Al 2 O 3 -SiO 2 is a compound, said pretreatment using said plasma-chemical process being carried out so as to remove silicon from a silicon-containing phase of said surface (2) of said material, The pretreatment with the plasma results in the pretreated surface (2) of the material being substantially α-Al 2 O 3 and In the boundary region (7) between the material and the aluminum oxide-containing layer (4), spike-like structures (6) are formed having tips (8) directed into the aluminum oxide-containing layer (4), said spike-like structures (6) having a width b between 50 and 200 nm and a height h between 100 and 500 nm; said width b being the width measured parallel to the interface between said material and said aluminium oxide containing layer (4); The method according to claim 1, wherein said height h is a height measured parallel to the layer thickness of said aluminum oxide-containing layer (4).
2. The plasma chemical process is 5×10 -3 mbar and 5 x 10 -2 2. The process according to claim 1, wherein the process is carried out at a total pressure of between 100 and 2000 mbar.
3. 3. The method according to claim 1 or 2, wherein the PVD method is reactive cathodic spark deposition or sputtering.
4. The method according to any one of claims 1 to 3, wherein the aluminium oxide containing layer (4) is applied as a substantially single-phase layer.
5. The method according to any one of claims 1 to 4, wherein the aluminium oxide containing layer (4) is deposited as a layer with metallic macroparticles.
6. The method according to any one of the preceding claims, wherein the aluminium oxide containing layer (4) comprises chromium, titanium, hafnium, yttrium, erbium, silicon and / or zirconium.
7. A step (S3) of heat treating the applied aluminum oxide-containing layer (4) at a temperature ranging between 900° C. and 1400° C. for a period of between 15 and 60 minutes. The method according to any one of claims 1 to 6, comprising:
8. A step (S4) of oxidizing the applied aluminum oxide-containing layer (4) using oxygen plasma. The method according to any one of claims 1 to 6, comprising:
9. Infiltrating the surface (2) of the material with an aluminum-containing material before pre-treating the surface (2) of the material using a plasma-chemical process. The method according to any one of claims 1 to 8, comprising:
Citation Information
Patent Citations
Alloy, protective coating for protecting a structural member against corrosion and oxidation at high temperatures and structural member
EP1780294A1
Method of operating pulsed arc evaporation source and vacuum processing apparatus having pulsed arc evaporation source
JP2008533311A
Al-cr-o-based coatings with higher thermal stability and producing method thereof
WO2019053257A1